Bridging the gap : disciplines, times, and spaces in dialogue. - Coppini, Costanza,; Cyrus, Georg,; Golestaneh, Hamaseh, (Access archaeology., 2022)
Three volumes present the proceedings of the 6th Broadening Horizons Conference, which took place at the Freie Universität Berlin from 24-28 June, 2019. This volume contains 14 papers from Session 4 - Crossing Boundaries: Connectivity and Interaction; and Session 6 - Landscape and Geography: Human Dynamics and Perceptions.